APLIKASI TEORI DOUBLE MOVEMENT FAZLU RAHMAN TERHADAP HUKUM MEMILIH PEMIMPIN NON-MUSLIM - Beta Firmansyah (Faculty of Ushuluddin UIN Syarif Hidayatullah Jakarta, 2019)
This article explain about the law choose non-Muslim leader. This article support hipotesa that choose the leader of the non-Muslim legal is may. This article background the back of the events that makes the al-Mā’idah: 51 as the basis of should not choose non-Muslim leader. Most of the mufassir using a view of a conservative in draw the conclusion the law of this verse, and they don’t look the context of when the law is relegated. Therefore, the authors filed theory Fazlu Rahman’s double movement to interpret the law choose non-Muslim leader. The conclusions of the author is choose the leader of the non-Muslim it may be with the condition of certain.